Innovations dans la gestion des universités : version française adaptée pour les pays francophones - Sanyal, Bikas C. (UNESCO, 2020)
Understanding the theoretical framework -- Overview of the book : case contributed by Noelle Jacquelin -- The multiple ethical paradigms -- Turbulence theory -- (Re)solving ethical dilemmas -- Security versus civil liberties : cases contributed by Susan H. Shapiro, Kelly D. Harbaugh, Mary Figura, Lisa Marie Waller -- Power versus accommodation in curriculum, instruction, and assessment : cases contributed by Stacy Aronow, James M. O'Connor, Robert Murphy, Corrine Caldwell -- Accountability versus responsibility : cases contributed by Rita Becker, Cynthia Renehan, Troy Wiestling, Kendall GlounerCommunity standards versus individual rights : cases contributed by Melissa Sterba, Christopher Lake, Shaun Little, Ellen Henderson Brown -- Equality versus equity : cases contributed by Albert Catarro, Jr., Jamie Shuda, W. Douglas Zander, Yvonette Marshall -- Personal vision versus authority : cases contributed by Terry McDonald, Alison Staplin, Maureen Linton, Emily Gross -- Rules, regulations, and policies versus individual needs and concerns in student teaching : cases contributed by David X. Fitt, Joseph P. DuCette, Sara Becker -- Introducing the new deel -- Control versus democracy.